2019
DOI: 10.1111/joim.12903
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic differences between Indian and Scandinavian women with gestational diabetes mellitus

Abstract: Objective Gestational diabetes mellitus (GDM) is a transient form of diabetes characterized by impaired insulin secretion and action during pregnancy. Population‐based differences in prevalence exist which could be explained by phenotypic and genetic differences. The aim of this study was to examine these differences in pregnant women from Punjab, India and Scandinavia. Methods Eighty‐five GDM/T2D loci in European and/or Indian populations from previous studies were assessed for association with GDM based on S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
3
11
0
Order By: Relevance
“…These findings are consistent with the premise that after proliferation, β-cells need to downregulate PAX4 to acquire a fully metabolic mature phenotype [80]. Supporting this likely role of HMG20A in islet adaptation processes during pregnancy, polymorphisms/mutations in HMG20A have also been associated with GDM as well as with postpartum abnormal glucose tolerance [11,28,113,114]. Given HMG20A function as an epigenetic modulator through regulation of the LSD1-CoREST complex, it will be of interest to determine whether long-term epigenetic modifications in offspring which are brought about during GDM may be a consequence of deregulated expression of HMG20A during pregnancy (see Section 3 and Figure 1).…”
Section: Hmg20a An Epigenetic Modulator Bridging Cns and Islets Respsupporting
confidence: 86%
See 1 more Smart Citation
“…These findings are consistent with the premise that after proliferation, β-cells need to downregulate PAX4 to acquire a fully metabolic mature phenotype [80]. Supporting this likely role of HMG20A in islet adaptation processes during pregnancy, polymorphisms/mutations in HMG20A have also been associated with GDM as well as with postpartum abnormal glucose tolerance [11,28,113,114]. Given HMG20A function as an epigenetic modulator through regulation of the LSD1-CoREST complex, it will be of interest to determine whether long-term epigenetic modifications in offspring which are brought about during GDM may be a consequence of deregulated expression of HMG20A during pregnancy (see Section 3 and Figure 1).…”
Section: Hmg20a An Epigenetic Modulator Bridging Cns and Islets Respsupporting
confidence: 86%
“…Currently GDM is one of the most common complications during pregnancy, with a prevalence reaching up to 27.5% in Southern Italian and an alarmingly 41.9% in Northern Indian women using the new and tighter diagnostic criteria recently adopted by the International Association of the Diabetes and Pregnancy Study Group [6,[9][10][11]. The growing prevalence of GDM is due, in part, to the increase in maternal overweight and the later age of conception [12][13][14].…”
Section: Metabolic Alterations During Pregnancy: Gestational Diabetesmentioning
confidence: 99%
“…Furthermore, rs11708067 is an eQTL in islets for both ADCY5 and the antisense transcript for ADCY5 supports the role of this SNP in impairment of insulin secretion in women with previous GDM, thus increasing the risk of diabetes postpartum. We also found that the ADCY5 rs11708067 genotype was associated with 2-h glucose level, consistent with the previous results from our group [16] as well as others [11,29].…”
Section: Discussionsupporting
confidence: 93%
“…Genome-wide association studies (GWAS) have revealed many genetic susceptibility loci for type 2 diabetes and related traits, such as insulin resistance and beta-cell dysfunction [10][11][12][13][14][15]. In addition, we have recently shown an association of the rs11708067 polymorphism in the ADCY5 (adenylate cyclase 5) gene with increased 2-h glucose levels and decreased homeostasis model assessment of beta-cell function (HOMA2-B) in Swedish women with GDM [16].…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest is the chromatin remodeling factor HMG20A that we recently reported to be essential for pancreatic islet beta-cell functional maturation and adaptation to stress conditions such as hyperglycemia and pregnancy [17,18]. Consistent with these functional data small nucleotide polymorphisms (SNPs) in the HMG20A gene have been associated to T2DM as well as gestational diabetes mellitus (GDM) in Asian/Indian and European populations [19][20][21][22][23][24][25]. HMG20A is also a key regulator of neuronal differentiation [26] by exerting global genomic changes through establishing active or silent chromatin [27].…”
Section: Introductionmentioning
confidence: 76%